Upaya Meningkatkan Kreativitas Anak Melalui Menggambar Di TK Pertiwi II Purworejo Kecamatan Blora Kabupaten Blora Tahun Pelajaran 2015/2016 - Puji Mulyani, Nunuk; , Dr. Darsinah, M.Si (2015)
The study aims to review the initials to review boost creativity learners in kindergarten Pertiwi II Purworejo Blora District of academic year 2015/2016 through Drawing Activity. Number wherewith and research methods husband is a Class Action Research, which consists differences 2 cycle. Subjects Recipients husband is a Student Activity Learners TK Pertiwi II Purworejo Blora as many as 12 of the Child. The Giver is the subject teacher at the school. Data was collected using the child creativity observation, interviews and field observations. Data analysis using comparative descriptive analysis techniques by comparing results cycle with any boarding costs indicator set. The indicator compared to the findings of Initial condition with the results achieved in each cycle, and a qualitative descriptive analysis results comparing the findings with observation Observation and reflection on pre-cycle, cycle i, and cycle ii. And the object of study subjects hearts husband is learners group B and a kindergarten teacher Pertiwi II Purworejo Blora. Learning Implementation husband Drawing Activity the given with the learners all students group B TK Pertiwi II Purworejo districts Blora Blora district on academic year 2015/2016. Based on the findings of research can be concluded that the husband through the activity draw it enhances creativity Kindergarten Students in kindergarten Pertiwi II Purworejo Blora academic year 2015/2016. Learning activities for the dilaksakan through three cycle. in every child learning activities are stimulated to carry out a review of creative always something. conclusion posted husband supported research is conducted te results showed an increase of 33.53% child creativity from pre cycle until cycle II.